STEM BASED EDUCATION FOR FUTURE LEARNING: CASE STUDY IN SMK UNGGULAN TERPADU PGII BANDUNG - Nuur Wachid Abdul Majid; Ahmad Fauzi; Taufik Ridwan; Rizki Hikmawan; Dian Permata Sari; Suprih Widodo (VANOS Journal of Mechanical Engineering Education, 2018)
This research aims to investigate of implementation STEM education in SMK Unggulan Terpadu PGII Bandung. The research used the qualitative case study approach. This research took place at SMK Unggulan Terpadu PGII Bandung. The informants in this research were the Vice Principal of the curriculum field in SMK Unggulan PGII and Lecture of Informatics Engineering. The data were collected through observations, in-depth interviews, and documentation. The technical analysis of the data referred to the analysis of Miles & Huberman interactive model, including data collection, data condensation, data display, and drawing and verifying conclusions. The result shows that STEM Education leads students to be able to solve problems, innovative, logical thinking, and insightful technology. So STEM will be implemented through: (1) Scientific-based learning; and (2) Achievement of Learning through Sustainable Learning.